The HMGB1–CXCL12 Complex Promotes Inflammatory Cell Infiltration in Uveitogenic T Cell-Induced Chronic Experimental Autoimmune Uveitis - Yun, Juan; Jiang, Guomin; Wang, Yunsong; Xiao, Tong; Zhao, Yuan; Sun, Deming; Kaplan, Henry J.; Shao, Hui (Frontiers in Immunology, 2017)
It is largely unknown how invading autoreactive T cells initiate the pathogenic process inside the diseased organ in organ-specific autoimmune diseases. In experimental autoimmune uveitis (EAU) induced by uveitogenic, interphotoreceptor retinoid-binding protein (IRBP)-specific T cells (tEAU) in mice, we have previously reported that high mobility group box 1 (HMGB1) is an early and critical mediator in induction of intraocular inflammation. Our present study explored the role of HMGB1 in intraocular inflammation, focusing on its role in recruiting cells into the eye. Our results showed that the supernatants from retinal explants either stimulated with HMGB1 or co-cultured with IRBP-specific T cells attracted leukocytes. Notably, HMGB1 antagonists blocked supernatant-induced chemoattraction when present from the start of co-culture, but not when added to the culture supernatants after co-culture, indicating that molecules released by HMGB1-treated retinal cells are chemoattractive. Moreover, CXCL12 levels in the co-culture supernatants were dependent on HMGB1, since they were increased in the co-culture and reduced when HMGB1 antagonists were added at the beginning of the co-culture. When either anti-CXCL12 Ab was added to the supernatants after co-culture or the mono-nuclear cells were pre-treated with Ab against CXCL12 specific receptor, CXCR4, chemoattraction by the co-culture supernatants was decreased. Finally, induction of tEAU was significantly inhibited by a CXCR4 antagonist, AMD3100, at the time of autoreactive T cell transfer. Our study demonstrates that, at a very early stage of intraocular inflammation initiated by uveitogenic autoreactive T cells, synergism between HMGB1 and CXCL12 is crucial for the infiltration of inflammation cells.